A Different Facet of p53 Function: Regulation of Immunity and Inflammation During Tumor Development - Shi, Di; Jiang, Peng (Frontiers in Cell and Developmental Biology, 2021)
As a key tran¬scription factor, the evolutionarily conserved tumour suppressor p53 (encoded by TP53) plays a central role in response to various cellular stresses. A variety of biological processes are regulated by p53 such as cell cycle arrest, apoptosis, senes-cence and metabolism. Besides these well-known roles of p53, accumulating evidence show that p53 also regulates innate immune and adaptive immune responses. p53 influences the innate immune system by secreted factors that modulate macrophage function to suppress tumourigenesis. Dysfunction of p53 in cancer affects the activity and recruitment of T and myeloid cells, resulting in immune evasion. p53 can also activate key regulators in immune signaling pathways which support or impede tumour development. Hence, it seems that the tumour suppressor p53 exerts its tumour suppressive effect to a considerable extent by modulating the immune response. In this review, we concisely discuss the emerging connections between p53 and immune responses, and their impact on tumour progression. Understanding the role of p53 in regulation of immunity will help to developing more effective anti-tumour immunotherapies for patients with TP53 mutation or depletion.